Radial Artery Forearm Flap Anomaly: A Rare Anomaly and the Importance of the Proximal Exploratory Incision - Venkataram, Aniketh; Ellur, Sunderraj; Muninarayana, Deepak; Joseph, Vijay (Journal of Hand and Microsurgery, 2016)
During a free radial forearm flap harvest, we encountered a variant anatomy of the arterial system. The brachial artery was found to travel with the median nerve and bifurcate 10 cm below the antecubital fossa, under cover of the pronator teres. The radial artery then emerged from the pronator and continued on its usual path. This anomaly has been reported only once thus far. We report this case to highlight our practice of always starting with a proximal exploratory incision to identify the anatomy before raising the flap, which is what enabled us to adapt to this variation with a satisfactory outcome.
Keywords: radial artery; free flap; variation; microsurgery